Experiment and Numerical Simulation of Wooden Door Frame - Eryu Zhu; Bin Wang; Dongqi Wei; Li Zhu (Advances in Materials Science and Engineering)
To prevent the wooden door frame of traditional rural houses from being stuck due to diamond deformation under earthquake and improve the seismic capacity of rural houses, an innovative method of reinforcing the angular displacement of the wooden door frame with channel steel and the diagonal brace is proposed. The rationality of the finite element simulation is demonstrated by comparing the results of finite element simulation and quasistatic test based on reinforced and unreinforced wooden door frame specimens. On the basis of the finite element model of wooden door frame, the seismic performance of channel type and diagonal brace thickness of reinforced wooden door frame and the seismic performance of friction coefficient of unreinforced wooden door frame are studied, respectively. The results show that the lateral stiffness and the lateral bearing capacity of the reinforced wooden door frame increase with the increase of channel steel type and the diagonal brace thickness. The height of the channel steel section of the seismic reinforcement structure should be half of the unreinforced structure. With the increase of the friction coefficient, the lateral bearing capacity of the unreinforced wooden frame increases, while the ductility of the unreinforced wooden frame decreases.